Quantum Governance and Pres. Ferdinand Marcos, Jr. - Emiliano T. Hudtohan (International Journal of Management and Education in Human Development, 2022)
Great Period of Change is within this period. Thus, the galactic invitation to create a new order for humanity is part of the challenge as the year 2023 announces the end of chaos and disharmony. As the new administration of Pres. Marcos, Jr; is taking shape with all the changes under his leadership, it is seen that the Newtonian-Cartesian-Weberian form of governance has to be reconsidered. On the horizon is the prospect of a Quantum Leadershift and Quantum Organization in the 21st century in a world that vulnerable, uncertain, complex, and ambiguous (VUCA). Quantum politics as new governance has been proposed; it is based on a new cosmology that updates the mechanistic approach to governance based on Newtonian-Cartesian science and the Weberian bureaucratic system. The reorganization of the Office of the President by President Ferdinand Marcos, Jr. is an opportunity to have leadership from the Newtonian-Cartesian-Weberian paradigm to the Quantum political paradigm. The reorganization of the Office of the President and the Office of the Vice President can have a Butterfly Effect on a new governance paradigm based on Quantum principles toward a Quantum constitution to fuel change for a Philippine Federal Government